From 2D to 3D patches on multifunctional particles: how microcontact printing creates a new dimension of functionality. Issue 12 (5th March 2018) - Zimmermann, Marc; John, Daniela; Grigoriev, Dmitry; Puretskiy, Nikolay; Böker, Alexander
Abstract : A straightforward approach for the precise multifunctional surface modification of silica particles with three-dimensional patches using microcontact printing is presented. Abstract : A straightforward approach for the precise multifunctional surface modification of particles with three-dimensional patches using microcontact printing is presented. By comparison to previous works it was possible to not only control the diameter, but also to finely tune the thickness of the deposited layer, opening up the way for three-dimensional structures and orthogonal multifunctionality. The use of PEI as polymeric ink, PDMS stamps for microcontact printing on silica particles and the influence of different solvents during particle release on the creation of functional particles with three-dimensional patches are described. Finally, by introducing fluorescent properties by incorporation of quantum dots into patches and by particle self-assembly via avidin–biotin coupling, the versatility of this novel modification method is demonstrated.